2021
DOI: 10.5296/wjbm.v7i1.17797
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Health Facility Financing Impact on Financial Management in Kaliua District Council, Tabora Tanzania

Abstract: This study assessed the implementation of Direct Health Facility Financing (DHFF) on financial management among primary health facilities of Kaliua District Council. The assessment conducted because Kaliua District is the one among 184 councils where the government introduced DHFF; the study adopted case study design whereby, both qualitative and quantitative approaches were used. A structured questionnaire, Interview, FDGs, Documentary review were used in obtaining data which were classified into planning pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
3
4
0
Order By: Relevance
“…Through questionnaires, interviews and FGDs for instance, HFGC members have revealed that they have been dealing with making sure nancial practices comply with nancial regulations, expenditure base on the budget and facility plan. This result is in line with other studies conducted in assessing whether DHFF improved performance in primary health facilities in Tanzania, it was found that community ownership and autonomy have increased to the extent that community health structures such as HFGCs are monitoring health serviced provision [35]. In the coast region in Kenya scal decentralization through DFF was found also to have increased the accountability of HFGCs in nancial management even though in some other facilities still HFGCs were not able to account for the devolved scal powers due to a lack of understanding of their roles [36], [37].…”
Section: Discussionsupporting
confidence: 91%
“…Through questionnaires, interviews and FGDs for instance, HFGC members have revealed that they have been dealing with making sure nancial practices comply with nancial regulations, expenditure base on the budget and facility plan. This result is in line with other studies conducted in assessing whether DHFF improved performance in primary health facilities in Tanzania, it was found that community ownership and autonomy have increased to the extent that community health structures such as HFGCs are monitoring health serviced provision [35]. In the coast region in Kenya scal decentralization through DFF was found also to have increased the accountability of HFGCs in nancial management even though in some other facilities still HFGCs were not able to account for the devolved scal powers due to a lack of understanding of their roles [36], [37].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, qualitative data from interviews and focus groups have revealed that HFGCs are more involved in their devolved functions as a result of DHFF implementation. The findings of this study are similar to those of earlier studies conducted in Tanzania to analyze the impact of DHFF in primary health care institutions, which revealed that DHFF led to enhanced community ownership, more autonomy, and improved financial management [8,30].…”
Section: Discussionsupporting
confidence: 86%
“…However, there have been few studies undertaken in Tanzania to investigate the functional condition of HFGCs in the setting of DHFF. Studies on DHFF have focused on the prospect and challenges of its implementation as well as the impact of DHFF on financial management 31–33 . Given the limitations of previous studies in informing about the status of HFGCs in carrying out their given powers and responsibilities in the context of the DHFF, this study was designed to evaluate the functioning of HFGCs in Tanzanian PHC facilities implementing the DHFF.…”
Section: The Introduction Of Health Facility Financing In Tanzaniamentioning
confidence: 99%
“…Studies on DHFF have focused on the prospect and challenges of its implementation as well as the impact of DHFF on financial management. [31][32][33] Given the limitations of previous studies in informing about the status of HFGCs in carrying out their given powers and responsibilities in the context of the DHFF, this study was designed to evaluate the functioning of HFGCs in Tanzanian PHC facilities implementing the DHFF. The study is essential because the findings may be beneficial in establishing a link between fiscal decentralization empowerment and its impact on HFGCs' functioning.…”
Section: The Introduction Of Health Facility Financing In Tanzaniamentioning
confidence: 99%